A short taxonomic note on the katydids from the genus Cercoteratura Gorochov, 2019 (Orthoptera: Tettigoniidae: Meconematinae), with a key to species - Tan, Ming Kai; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2020)
The tribe Meconematini is a monophyletic and speciose group of slender and predatory katydids from the Indomalayan and Palearctic region (Mugleston et al., 2018). It is especially species-rich from the biodiverse regions of Southeast Asia (Cigliano et al., 2020) but also elusive, as many new species and genera are still being discovered from tropical Southeast Asia (e.g., Tan & Wahab, 2018a; Gorochov, 2019). As more material is accumulated, new understandings of how species are related and/or classified emerged. A species of Meconematini was first described from the primary dipterocarp forest of Kuala Belalong Field Studies Centre in Brunei Darussalam, Borneo among a few other related species (Tan et al., 2017, Tan & Wahab, 2018): Kuzicus mirabilis Tan & Wahab, 2018. This species exhibits the deep posteromedian notch of the last male tergite characteristics of Xiphidiopsis Redtenbacher, 1891 but differs by the presence of sclerotized yoke-like epiphallus, typical of Kuzicus Gorochov, 1993 (see Tan & Wahab, 2018a). A year later, A. V. Gorochov erected a new genus Cercoteratura Gorochov, 2019 based on a new species Cercoteratura variegata Gorochov, 2019 from Sumatra and Borneo (Gorochov, 2019). Three other species were also included in this genus, mainly from Sumatra and Thai-Peninsula. We found that the species from Brunei Darussalam could also belong to this genus and represent the eastern-most record of this genus. We provide a key to known species of Cercoteratura, although it is likely that this genus is more speciose than currently known. We also present a morphological comparison of the three similar genera Cercoteratura, Kuzicus and Xiphidiopsis.